Utility of Doppler sonography for renal artery stenosis screening in obese children with hypertension. Issue 4 (25th March 2018) - Makhija, Pooja; Wilson, Christopher; Garimella, Sudha
Abstract : Pediatric hypertension guidelines recommend Doppler renal ultrasonography as a screening study for the evaluation of possible renal artery stenosis (RAS) in normal‐weight children ≥ 8 years of age who are suspected of having RAS and who will cooperate with the procedure. Obese children are excluded because of technical and vascular concerns. There are no data on RI in obese children. This is a retrospective review of children aged 1.5‐18 who received Doppler imaging studies over a 10‐year period. A total of 174 patients were studied. There was no significant difference between the RI values based on BMI. Of the 174 individuals in the study 22 obtained follow‐up CT/MRA after abnormal Doppler ultrasounds. On advanced imaging 3 were confirmed to have RAS. Obesity does not seem to influence RI.RI alone should not be used as a screening tool for RAS. An approach toward diagnosis is suggested based on BMI, renin levels, and ultrasound.